For a Healthy Life, the Role of Aahara – Vihara in Ritucharya - Sharma, Manish Kumar; Kumari, Anita; Khan, Iqbal; Sharma, Ashok Kumar; Sharma, K L; Meena, Rekhraj; Nigam, Ayushi (International Research Journal of Ayurveda & Yoga, 2022)
There are three seasons in general: winter, summer, and rainy season. Six seasons are considered in Ayurveda: Vasant, Grishma, Varsha, Sharad, Hemant, and Shishir. The 12 months of the year have been classified into these seasons by Acharya Sushrut. In Visarga, there are two seasons: the first is when the sun goes towards the north, and the second is when the sun moves towards the south. These are referred to as Adanakala And Visargakala, respectively. The input period has winter (shishir), spring (vasant ritu), and summer (grishma ritu) seasons, while the Visarga period has varsha(monsoon), autumn (sharad ritu) and (Pri-winter) Hemant seasons. The Sun is strong and the moon is week at the moment of the exchange. The Moon is powerful and the Sun is weak during the Visarga era. The shishir and hemant ritu is of great strength, the vasant and sharad is of medium strength and the varsha and grishma is of low strength.